Gold(I)‐Catalyzed and PTSA‐Promoted Cycloisomerization of Ynamides to Access Pyrrole Substituted α, β‐Unsaturated Ketones. Issue 4 (4th January 2023) - Choudhary, Shivani; Gayyur; Ghosh, Nayan
Abstract: Substituted pyrroles are prevalent aromatic ring systems encountered in numerous natural products and bioactive molecules. Herein, a novel ynamide scaffold has been designed, synthesized and subsequently applied to an unprecedented gold‐catalyzed and para ‐toluenesulfonic acid (PTSA)‐assisted cascade cycloisomerization reaction for the synthesis of β‐pyrrole substituted α, β‐unsaturated ketones. Notably, the reaction is stereoselective, offering E ‐isomer as major product with low to moderate yield. Abstract : In this work, a new ynamide scaffold has been designed, synthesized and later applied in a gold‐catalyzed cycloisomerization reaction to access pyrrole containing α, β‐unsaturated ketones in low‐to‐moderate yields. Interestingly, the trans product has been obtained as a major isomer.